Analysis of coaching science research published from 1970-2001 - Gilbert, W. D.; Trudel, P. (Research Quarterly for Exercise and Sport, 2004)
The study followed a four-phase design. In Phase I an exhaustive search was conducted for all English language coaching research published in journals from 1970 to 2001. In Phase II, copies of the research were obtained. An expert panel conducted a manual search and a review in Phase III to address validity. Analysis of the research was completed in Phase IV (Culver, Gilbert, & Trudel, 2003; Silverman & Skonie, 1997). Over 1,100 articles were reviewed, and 610 met the inclusion criteria. Selected findings include: (a) a relatively low mean spread across many journals, (b) a focus on coaching behavior using quantitative methodologies, and (c) a primary emphasis on team sports in school contexts.